Taxifolin stability: In silico prediction and in vitro degradation with HPLC-UV/UPLC-ESI-MS monitoring - Fernanda Cristina Stenger Moura; Carmem Lúcia dos Santos Machado; Favero Reisdorfer Paula; Angélica Garcia Couto; Maurizio Ricci; Valdir Cechinel-Filho; Tiago J. Bonomini; Louis P. Sandjo; Tania Mari Bellé Bresolin (Elsevier, 2021)
Taxifolin has a plethora of therapeutic activities and is currently isolated from the stem bark of the tree Larix gmelinni (Dahurian larch). It is a flavonoid of high commercial interest for its use in supplements or in antioxidant-rich functional foods. However, its poor stability and low bioavailability hinder the use of flavonoid in nutritional or pharmaceutical formulations. In this work, taxifolin isolated from the seeds of Mimusops balata, was evaluated by in silico stability prediction studies and in vitro forced degradation studies (acid and alkaline hydrolysis, oxidation, visible/UV radiation, dry/humid heating) monitored by high performance liquid chromatography with ultraviolet detection (HPLC-UV) and ultrahigh performance liquid chromatography-electrospray ionization-mass spectrometry (UPLC-ESI-MS). The in silico stability prediction studies indicated the most susceptible regions in the molecule to nucleophilic and electrophilic attacks, as well as the sites susceptible to oxidation. The in vitro forced degradation tests were in agreement with the in silico stability prediction, indicating that taxifolin is extremely unstable (class 1) under alkaline hydrolysis. In addition, taxifolin thermal degradation was increased by humidity. On the other hand, with respect to photosensitivity, taxifolin can be classified as class 4 (stable). Moreover, the alkaline degradation products were characterized by UPLC-ESI-MS/MS as dimers of taxifolin. These results enabled an understanding of the intrinsic lability of taxifolin, contributing to the development of stability-indicating methods, and of appropriate drug release systems, with the aims of preserving its stability and improving its bioavailability.